CCD SDSS Photometry of Poorly Studied Star Clusters in the Large Magellanic Cloud - Piatti, Andres Eduardo (2014)
We present for the first time CCD SDSS푔푟photometry, obtained at the Gemini South telescope with the GMOS attached, of stars inthe field of the poorly studied star clusters NGC1768, HS 85, SL 676, NGC2107, NGC2190, and SL 866, which are distributed in themain body of the Large Magellanic Cloud. We applied a subtraction procedure to statistically clean the cluster CMDs from field starcontamination. In order to disentangle cluster features from those belonging to their surrounding fields, we applied a subtractionprocedure which makes use of variable cells to reproduce the field star color-magnitude diagrams (CMDs) as closely as possible. Wethentraced theirstellardensity radialprofilesfromstarcountsperformedover thecleaned field starsdataset and derivedtheir radii.Using the cleaned cluster CMDs, we estimated ages and metallicities from matching theoretical isochrones computed for the SDSSsystem. The studied star clusters have ages from 0.1 up to 2.0Gyr and are of slightly metal-poor metal content ([Fe/H]≈−0.4dex).